Gait in depression: a bibliometric analysis and knowledge mapping of research trends over the past 20 years - Kan, Shao-Kui; Chen, Nuan-Nuan; Peng, Bo; Zhang, Ying-Li (Frontiers in Psychiatry, 2025)
BackgroundDepression carries a high risk of suicide, with many individuals failing to receive treatment due to diagnostic challenges and stigma. Gait is linked to depression, underscoring the importance of gait analysis in the diagnosis and treatment of depression. However, comprehensive and objective evaluations of the current research on gait in depression are lacking. This study aims to use bibliometric analysis and knowledge mapping to clarify research trends and status.ObjectiveThis study employs bibliometric analysis to investigate gait in depression, summarizing historical and current trends while predicting future directions. This analysis will aid researchers and policymakers in understanding evolving trends and prioritizing research resources effectively.MethodsWe conducted a computer-based search of the Web of Science core collection to identify articles and reviews related to depression and gait. Bibliometric analysis, involving the analysis of aspects such as countries or regions, institutions, authors, journals, keywords, and references, was performed using Excel 365, CiteSpace, and VOSViewer.ResultsThe analysis included a total of 848 publications from 2005 to 2024. The results showed a phased increase in publications, peaking in 2020 with 102 publications, followed by a gradual decline. Citations in this field showed a yearly increase, peaking in 2022 with 3920 citations before subsequently declining. The United States was identified as the most productive and influential country in this field, with the highest number of publications and citations. They have the institutions with the highest publications and citations. Leading authors in this field include Verghese Joe, Shimada Hiroyuki; and Rochester Lynn. Key journals include BMC Geriatrics, Journals of Gerontology Series and Medical Sciences, and Journal of the American Geriatrics Society. Frequently mentioned keywords in this field are depression, gait, gait speed, older adults, and dementia. Identification of distinctive gait patterns in depression, gait characteristics in the elderly, association between gait and cognitive decline, and interventions for abnormal gait constitute current research forefronts in this domain.ConclusionsThis study is the first to utilize bibliometrics to visualize research in the field of gait-related depression. It reveals research trends and frontiers, providing valuable references for scholars seeking important research topics and potential collaborators.